Pengaruh Non Performing Loan, Loan to Deposit Ratio, Dan Biaya Operasional Dan Pendapatan Operasional Terhadap Profitabilitas Bank Pembangunan Daerah - Nurfani Azimawati Nurfani Azimawati (Universitas Sains dan Teknologi Komputer, 2023)
The role of banking is currently very important in the financial system. A good financial system will have a good effect on banking performance which is projected by the Return On Assets (ROA) ratio. The purpose of this study is to examine and analyze the effect of Non Performing Loans (NPL), Loan to Deposit Ratio (LDR), and Operational Costs and Operating Income (BOPO) on banking profitability. The data used in this study were obtained from financial reports from the Otoritas Jasa Keuangan (OJK) website www.ojk.id for 2019 – 2021. Sampling used the Purposive Sampling method, with a total sample of 26 BPDs and only 24 BPDs that met the following criteria: research sample. Sample data were obtained using Microsoft Excel and SPSS. The analytical method used in this research is multiple linear regression analysis method. The results of the study show that in 2019 – 2021, the NPL ratio has no effect on ROA, LDR has a positive effect on ROA, and BOPO has a negative effect on ROA.